Augmented reality collaborative medical displays (ARC-MeDs) for multi-user surgical planning and intra-operative communication - Song, Tianyu; Yu, Kevin; Eck, Ulrich; Navab, Nassir (Computer Methods in Biomechanics and Biomedical Engineering : Imaging & Visualization, 2022)
Digital Displays are integral to modern systems and serve as the primary visual human-computer interface. A physical monitor is a typical example for showing computer-generated information to a person–as long they are located directly in front of them. In an operating room, however, people may be unable to move freely or communicate only based on verbal communication due to noise pollution. Furthermore, mobile and connected editing and sharing of the same content on the go is currently not readily available. Therefore, we propose Augmented Reality Collaborative Medical Displays for duplicating any displayed content as a virtual monitor hovering in space in the real world. Our method replicates any user input on the virtual representation onto the original physical monitor. We put forward a use case in planning a surgical intervention of the abdomen with intra-operative CT imaging. Moreover, we demonstrate how a medical immersive teleconsultation system utilises our method for meaningful interactions. Finally, we evaluate our method with multiple display resolutions. Based on our observations from the use cases and quantitative evaluation, we believe our proposed concept facilitates the integration of future collaborative medical applications.
CRIS-Team Scopus Importer:2023-03-08
Keywords: co-located collaboration; mixed reality; Multi-display system; surgical planning